Syntheses of methylenolactocin and nephrosterinic acid via diastereoselective acylation and chemoselective reduction-lactonization - Rattana Jongkol (2018)
The syntheses of methylenolactocin, nephrosterinic acid and their derivatives can be achieved by using the efficient diastereoselective acylation of dimethyl itaconate-anthracene adduct followed by tandem chemoselective reduction-lactonization. © 2009 Elsevier Ltd. All rights reserved.